1994
DOI: 10.1126/science.8052857
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Mammalian Cells by Constitutively Active MAP Kinase Kinase

Abstract: Mitogen-activated protein (MAP) kinase kinase (MAPKK) activates MAP kinase in a signal transduction pathway that mediates cellular responses to growth and differentiation factors. Oncogenes such as ras, src, raf, and mos have been proposed to transform cells by prolonging the activated state of MAPKK and of components downstream in the signaling pathway. To test this hypothesis, constitutively active MAPKK mutants were designed that had basal activities up to 400 times greater than that of the unphosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
1,089
5
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,310 publications
(1,133 citation statements)
references
References 44 publications
37
1,089
5
2
Order By: Relevance
“…Both T507K SHP-2 and the leukemia-specific E76K SHP-2 are capable of eliciting aberrant activation of RAF1. Although constitutive activation of the RAS-RAF-ERK pathway intimately relates with NIH3T3 transformation (Mansour et al, 1994), the failure of E76K SHP-2 to transform NIH3T3 cells indicates that aberrant activation of the RAS-RAF-ERK pathway per se is not sufficient for the transformation of NIH3T3 cells. In this regard, we also investigated the effects of wild-type SHP-2, T507K SHP-2 and E76K SHP-2 on another RAS-effector pathway, the PI3K-AKT pathway and found that none of these SHP-2 mutants significantly modifies AKT activity when expressed in NIH3T3 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Both T507K SHP-2 and the leukemia-specific E76K SHP-2 are capable of eliciting aberrant activation of RAF1. Although constitutive activation of the RAS-RAF-ERK pathway intimately relates with NIH3T3 transformation (Mansour et al, 1994), the failure of E76K SHP-2 to transform NIH3T3 cells indicates that aberrant activation of the RAS-RAF-ERK pathway per se is not sufficient for the transformation of NIH3T3 cells. In this regard, we also investigated the effects of wild-type SHP-2, T507K SHP-2 and E76K SHP-2 on another RAS-effector pathway, the PI3K-AKT pathway and found that none of these SHP-2 mutants significantly modifies AKT activity when expressed in NIH3T3 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to pBabe cells, HU produced higher levels of Erk activation in MEK1Q56P cells, which requires higher doses of U0126, the most potent MEK inhibitor (Krepinsky et al, 2002), to block the Erk activation (Figure 1b). Conversely, ectopic expression of a dominant-negative mutant MEK1 (MEK1K97M) (Mansour et al, 1994) attenuated HUinduced Erk activation (Figure 1c). Taken together, these data reveal that MEK1 plays a role in HU-induced Erk activation.…”
Section: Hu Activates Erk Kinase Via Mek1mentioning
confidence: 99%
“…To determine the point at which LIMK1 inhibits the Ras-induced di erentiation signaling pathway, we examined the e ect of overexpression of DK-HA on activated MAPKK-induced di erentiation of PC12 cells. The expression plasmid pRc-CMV-DNSESE containing Xenopus DNSESE was used for expression of constitutively activated MAPKK, in which the Nterminal negative regulation domain (residues 32 ± 51) was deleted and two activating phosphorylation sites (Ser218 and Ser222) were replaced by glutamic acid residues (Gotoh et al, 1995;Mansour et al, 1994). In the transient transfection assay with the b-Gal reporter plasmid, DNSESE induced neuronal di erentiation of PC12 cells in 57% of blue cells (Figure 3).…”
Section: Constitutively Activated Mapkk-induced Pc12 DI Erentiation Imentioning
confidence: 99%